Social connectedness among university students: an investigation using the social connectedness scale (scs) and demographic factor - Bariyyah, Khairul; Arbin Janu Setiyowati; Otto Fajarianto; Arif Prastiawan; Maizura, Nining; Abu Yazid Abu Bakar (COUNS-EDU: The International Journal of Counseling and Education, 2024)
This study aims to measure the level of social connectedness among students using the Social Connectedness Scale (SCS) and explore the relationship between social connectedness and demographic factors such as gender, relationship status, semester level, and participation in campus organizations. This research employed a quantitative method with a descriptive and comparative approach. A total of 464 students from the Faculty of Education at Universitas Negeri Malang were selected through stratified random sampling. The primary instrument used was the Social Connectedness Scale (SCS), and demographic data were collected via a questionnaire. Data analysis was conducted using ANOVA and Independent Samples T-Test to evaluate differences in social connectedness based on demographic variables. The results indicated significant differences in social connectedness based on participation in organizations, but no significant differences were found based on gender or relationship status. These findings highlight the importance of involvement in campus organizations to enhance students' social connectedness and well-being.